The Document Q: In Search of the Lost Group - Álvarez Cineira, David (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Provided that, according to a great amount of authors, the Document Q would represent the earliest document of primitive Christianity, it is much understandable the interest on identifying the Christian group that composed it. For some researchers, we would be dealing with a sort of Galilean Christianity, diverse and in contrast with the community of Jerusalem, a group lost in our historical accounts. Are there real possibilities of success in these efforts? This article reviews recent scholarship on the matter and the conditions that can make it possible to identify such a group.